“Civil disobedience as a moral response to lockdown regimes” - Dlamini, Armstrong (My University, 2021)
In the wake of the Covid-19 pandemic, the South African Government faced the predicament of making a choice between imposing a lockdown and opening up the economy. It chose the former in line with utilitarian considerations to save as many lives as possible and subsequently promulgated lockdown regulations to control the movement of people and curb infections. However a host of lockdown restrictions were irrational and unreasonable. The public reacted through acts of civil disobedience which were premised on people’s claims to civil liberties and the right to disobey laws that are irrational. This paper argues that some of the protests against the lockdown can be characterized as civil disobedience and that on Rawls’ terms, it would have been justified
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Applied Ethics for Professionals to the Faculty of Humanities, University of the Witwatersrand, 2021